2013
DOI: 10.1111/bjhp.12061
|View full text |Cite
|
Sign up to set email alerts
|

Minding the body: Psychotherapy and cancer survival

Abstract: What is known? Stress and support have been thought to be related to cancer risk and progression, but evidence has been mixed. Depression is a natural co-morbid condition with cancer. It has not been clear how stress and support could physiologically affect the rate of cancer progression. Immune function was not thought to have much relevance to cancer progression. Few other physiological mechanisms linking stress to cancer progression were known. What does this paper add? There is evidence from 15 RCTs indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 203 publications
2
24
0
1
Order By: Relevance
“…Also, we find that shorter term exposure to road traffic noise (1 year) seems slightly stronger associated with breast cancer than longer term exposure (10 years). A possible explanation might be that noise‐induced stress affects progression of breast tumors and not tumor initiation, which corresponds to overall findings from epidemiological studies on psychosocial stress and breast cancer …”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Also, we find that shorter term exposure to road traffic noise (1 year) seems slightly stronger associated with breast cancer than longer term exposure (10 years). A possible explanation might be that noise‐induced stress affects progression of breast tumors and not tumor initiation, which corresponds to overall findings from epidemiological studies on psychosocial stress and breast cancer …”
Section: Discussionsupporting
confidence: 62%
“…Glucocorticoids are involved in a variety of cellular and physical processes that might promote tumor progression including apoptosis, immune response and angiogenesis . Though psychosocial stress has been suspected of affecting breast cancer risk and progression for many years, epidemiological studies have failed to find any clear relationship with risk for breast cancer, whereas a number of studies have indicated that psychosocial stress and support may affect the course of breast cancer progression …”
mentioning
confidence: 99%
“…[22] The majority of such studies have focused on breast cancer survivors; many have attempted to define the mechanisms involved in improving survival with psychosocial intervention including the hypothalamic-pituitary axis, the immune system, disruption of other circadian rhythms such as sleep/activity, the sympathetic-adrenal-medullary system, and the relationship between stress and p53 gene expression. [23] However, there is significant controversy around whether or not BPSI improves survival. [24] This has resulted from factors including lack of consistency in definition of intervention, [25] and inadequate sample sizes.…”
Section: Discussionmentioning
confidence: 99%
“…Various clinical and epidemiological studies have demonstrated that tumour growth, progression, and metastasis are associated with reported patient stress, depression, and anxiety, as well as with limited perceived social support and poor coping mechanisms (Lillberg et al, 2003;Spiegel, 2002;Spiegel & Giese-Davis, 2003). Pathways linking stress reduction to changes in endocrine, immune and autonomic nervous system function and pathways linking gene expression to cancer progression are being studied (Rutter et al, 2008;Spiegel, 2013).…”
Section: Psychophysiology: How Psychosocial Interventions Might Impacmentioning
confidence: 99%